1999
DOI: 10.1002/(sici)1099-1387(199907)5:7<323::aid-psc201>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Linear analogues derived from the first EGF-like domain of human blood coagulation factor VII: enhanced inhibition of FVIIa/TF complex activity by backbone modification through aspartimide formation

Abstract: Coagulation factor VII bound to its cofactor tissue factor is the physiological initiator of blood coagulation. The interaction between factor VII and tissue factor involves all four of the structural modules found in factor VII, with the most significant contribution coming from the first EGF-like domain. In this study, the synthesis and biological activity of several analogues derived from the first EGF-like domain of FVII comprising the sequence 45-83 are reported on. The six cysteine residues found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…One recurrent problem we have observed during the assembly of EGF‐like domains was the formation, often in high yield, of aspartimide ring byproducts (23). Analysis of the amino acid sequence revealed several potentially sensitive areas where an asparagine or aspartic acid residue was positioned at the N ‐terminal side of a glycine residue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One recurrent problem we have observed during the assembly of EGF‐like domains was the formation, often in high yield, of aspartimide ring byproducts (23). Analysis of the amino acid sequence revealed several potentially sensitive areas where an asparagine or aspartic acid residue was positioned at the N ‐terminal side of a glycine residue.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the amino acid sequence revealed several potentially sensitive areas where an asparagine or aspartic acid residue was positioned at the N ‐terminal side of a glycine residue. In vitro data of the EGF‐like analogues indicated that one of the ring‐opened β‐aspartic acid peptides, isolated as an impurity during the synthesis, possessed increased biological activity compared with the parent sequence (23). We were therefore interested in synthesizing analogues where the β‐Asp residue was introduced deliberately during the assembly of the peptide in order to compare and contrast the structure and biological activity of this product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown the functional importance of both EGF domains of FVII in the induction of coagulation via the extrinsic pathway (13,14). Furthermore, we reported short peptides derived from the EGF‐2 domain, which possess anticoagulant activity (15).…”
mentioning
confidence: 99%